2014
DOI: 10.1097/mao.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Focal Sclerosis of Semicircular Canals With Severe DFNA9 Hearing Impairment Caused by a P51S COCH-Mutation

Abstract: Eight of 9 subjects with the same P51S mutation in the COCH gene showed similar radiologic lesions, affecting the PSCC in the majority of the cases. These radiologic abnormalities occurred in more advanced stages of the otovestibular deterioration, supporting the hypothesis that these lesions might represent the end phase of a low-grade chronic inflammation or protein deposition. A new phenotypic and characteristic radiologic feature of DFNA9 has been discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 16 publications
5
32
1
Order By: Relevance
“…The hearing losses are sensorineural. Note the downsloping character of the thresholds Complete physical, serologic, hematologic, urinary, cardiac, renal and ophthalmologic examinations were unremarkable for both brothers and proband's AI-010 Computed tomography (CT) and magnetic resonance imaging (MR) did not show any typical focal sclerotic lesions in any of the semicircular canals similar described in COCH c.151 C>T (P. Pro51Ser) positive patients [9]. Videonystagmography (VNG) showed bilateral symmetrical, but marked hyporeflective caloric response with normal, albeit high amplitudes on pendular chair responses in proband AI-010.…”
Section: Case Detailsmentioning
confidence: 73%
“…The hearing losses are sensorineural. Note the downsloping character of the thresholds Complete physical, serologic, hematologic, urinary, cardiac, renal and ophthalmologic examinations were unremarkable for both brothers and proband's AI-010 Computed tomography (CT) and magnetic resonance imaging (MR) did not show any typical focal sclerotic lesions in any of the semicircular canals similar described in COCH c.151 C>T (P. Pro51Ser) positive patients [9]. Videonystagmography (VNG) showed bilateral symmetrical, but marked hyporeflective caloric response with normal, albeit high amplitudes on pendular chair responses in proband AI-010.…”
Section: Case Detailsmentioning
confidence: 73%
“…During the last decades, many genotype-phenotype observational reports with auditory and vestibular testing have shown limited variability across subjects and helped to characterize DFNA9 (5,13,14). Recently, JanssensdeVarebeke et al described a correlation between hearing loss and radiological abnormalities in patients with DFNA9, specifically with a P15S mutation in the COCH gene (9). This study suggested that radiological findings and the degree of hearing loss are both linked to the stage of this hereditary disease (9).…”
Section: Discussionmentioning
confidence: 90%
“…This loss of fibrocytes leading to accumulation of acellular substance that probably consists of misfolded COCH protein may be the cause of cytotoxicity (6)(7)(8). Radiologic abnormalities on computed tomography (CT), including narrowing or sclerosis of the SCC, and T2-weighted magnetic resonance imaging (MRI), including signal loss in the SCC, have already been reported as a biomarker in carriers of the P51S mutations in the COCH gene (9). The authors have shown a correlation of these lesions with advanced stages of sensorineural hearing loss, suggesting these lesions to be secondary to an advanced inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…At the best of our knowledge there are no studies that have already investigated MR findings of DFNA9 ears by a 3 Tesla scanner and using pre-and postcontrast 3D-FLAIR sequences, which has been demonstrated to be an emerging technique able to add new insights about different inner ear pathologies, such as sudden hearing loss and Ménière's disease [Conte et al, 2017]. Another study had attempted to assess the morphology of DFNA9 ears by computed tomography and by MRI using classic heavily-T2 MR sequence, which is, unfortunately, less sensitive in detecting the changes in inner ear structures [De Varebeke et al, 2014].…”
Section: Discussionmentioning
confidence: 99%